2020 global food outlook: Trends, alternatives, and choices - Rosegrant, Mark W.; Paisner, Michael S.; Meijer, Siet; Witcover, Julie (International Food Policy Research Institute, 2001)
Government officials and representatives of aid agencies are continually making decisions about how to spend their resources. It is easy to lose sight of the fact that each decision to be made represents a fork in the road, and each investment is a step in the direction of a future that will bring a healthy, sustainably produced diet to more people—or to fewer. This report shows just how, and how much, certain policy decisions and social changes will affect the world’s future food security. It projects the likely food situation in 2020 if the world continues on more or less its present course, and it then shows how alternative choices could produce a different future. Even rather small changes in agricultural and development policies and investments, it turns out, can have wide-reaching effects on the number of poor and undernourished people around the world. A world of less poverty, greater food security, and a healthier environment is possible, but it will not come about without explicit policy steps in that direction. 2020 Global Food Outlook is the latest in a series of world food projections based on a model developed at IFPRI beginning in 1992.The model has been updated and expanded periodically since then as a way of painting an ever-clearer picture of the global food situation in 2020. More details about the simulations in this report are available in a comprehensive monograph titled Global Food Projections to 2020: Emerging Trends and Alternative Futures.